EFFECT OF DIFFERENT CARBON AND NITROGEN SOURCES ON SOLUBILIZATION OF INSOLUBLE INORGANIC PHOSPHATE BY PSYCHROTOLERANT BACTERIAL STRAINS - PALLAVI, KUMARI PUNAM; GUPTA, PRAKASH CHANDRA (The Bioscan, 2013)
Most agricultural soils contain large reserves of phosphorus (P), a considerable part of which accumulates as a consequence of regular applications of P fertilizers. However, a greater part of soil phosphorus, approximately 95–99% is present in the form of insoluble phosphates and hence cannot be utilized by the plants. Phosphate solubilizing microorganisms convert insoluble phosphates into soluble forms generally through the process of acidification, chelation and exchange reactions. Thus, such microorganisms may not only compensate for higher cost of manufacturing fertilizers in industry but also mobilizes the fertilizers added to soil. In the present study Pseudomonas lurida isolated from agriculture soil, having potential to solubilize insoluble inorganic phosphates at low temperature was characterized. Phosphate solubilization was related to pH decrease caused by growth of bacteria in medium containing glucose as carbon source. Strains show diverse levels of phosphate solubilization activity in liquid broth culture in presence of various carbon and nitrogen sources. TCP (Tri-calcium phosphate) solubilization with different carbon sources irrespective of incubation period can be related in the following order: glucose, maltose, sucrose, galactose, xylose both at ambient as well as 10oC. The pH changes from neutral to acidic with all carbon sources in presence of TCP. Regarding TCP, solubilization with different nitrogen sources maximum solubilization was recorded in the presence of ammonium sulphate. Pseudomonas lurida showed maximum phosphate solubilizing with glucose as carbon source and ammonium sulphate as nitrogen source. TCP solubilization in liquid medium was significantly high.